Respuesta :
Step-by-step explanation:
x−y+2z=0
Step 1: Add y to both sides.
x−y+2z+y=0+y
x+2z=y
Step 2: Add -2z to both sides.
x+2z+−2z=y+−2z
x=y−2z
Answer:
x=y−2z
x−2y+3z=−1
Step 1: Add -x to both sides.
x−2y+3z+−x=−1+−x
−2y+3z=−x−1
Step 2: Add -3z to both sides.
−2y+3z+−3z=−x−1+−3z
−2y=−x−3z−1
Step 3: Divide both sides by -2.
−2y/−2 = −x−3z−1/−2
y= 1/2 x+ 3/2 z+ 1/2
Answer:
y= 1/2 x+ 3/2 z+ 1/2
2x−2y+z=1
Step 1: Add 2y to both sides.
2x−2y+z+2y=1+2y
2x+z=2y+1
Step 2: Add -z to both sides.
2x+z+−z=2y+1+−z
2x=2y−z+1
Step 3: Divide both sides by 2.
2x/2 = 2y−z+1/2
x=y+ −1/2 z+ 1/2
Answer:
x=y+ −1/2 z+ 1/2
Answer:
X = 4/3
Y = 2/3
Z = - 1/3
Step-by-step explanation:
Multiply the first equation by -1 =
-x + y - 2z = 0
Add this equation to the second equation =
(x-2y+3z = - 1) + (-x + y - 2z = 0) =
-y + z = -1
Multiply the first equation by -2=
-2x+2y-4z = 0
Add this equation to the third equation =
(-2x+2y-4z=0) + (2x-2y+z=1) =
-3z = 1
z = - 1/3
(-y + z = - 1 ) = -y - 1/3 = -1
-1/3 + 1 = y
y = 2/3
Substitute z = -1/3 and y = 2/3 in an equation to find the x value.
x - 2/3 + 2(-1/3) = 0
x -2/3 - 2/3 = 0
x -4/3 = 0
x = 4/3